Confucius Institute: Soft Power and Cultural Diplomacy - Nurhusna, Nadia; Sakinah, Zaskia (Confucius Institute Universitas Sebelas Maret, 2024)
Today advances in technology and human intelligence have made many countries flock to increase their soft power in the international arena. The Chinese government is no exception, actively trying to increase soft power through various programs. One of these efforts can be seen with the establishment of the Confucius Institute. China founded the Confucius Institute to promote Chinese language and culture abroad. These efforts include spreading the Mandarin language, holding cultural exhibitions, and collaborating academically with various countries. This research aims to analyze the Confucius Institute's role in increasing China's soft power. This research uses a qualitative approach by collecting and evaluating data through supporting literature, including academic journal articles and investing news. The Confucius Institute effectively increases the general public's understanding of China. However, there are concerns that Confucius Institutes exist to influence the political views and foreign policies of host countries. Overall, the Confucius Institute is essential to China’s cultural diplomacy efforts, but its approach must maintain a balance between cultural promotion and sensitivity to host country contexts.